Juridical Review of the Constitutional Rights of Former Convicts Obtaining Parole in Nominating Regional Head Elections - Malau, Paulus Dedi Dores; Ahmad, Suparji; Rifai, Anis (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This article focusing on the ex-convict with sentence of 5 (five) years or more with his position as will candidate contestant election general and chief area. In study This writer lift a number of problem related laws with provisions for a 5 (year) cooling off period for ex- convict, that provision the own Lots allusion with Human Rights Man, Constitution, as well rule related legislation with election general and election head area. Methodology research used in study This that is juridical normative with do approach to theories laws, regulations, as well analysis cases that have been own strength law fixed (inkracht). As for sources internal primary law study This namely the 1945 NRI Constitution, law election head area, law election, verdict Court Constitution, as well decision relevant Supreme Court with case in study. That in policy gap of 5 (years) for ex-prisoner will arise problem new if “ex-prisoner” at the time has served 2/3 of the sentence Then submit liberation conditional so that must serve the legal term addition in the form of a trial period for 1 (one) year. Even post Decision Court Constitution Number 42/PUU-XIII/2015 and the Constitutional Court 56/PUU-XVII/2019, this condition is becoming increasingly controversial, because precisely give rise to uncertainty law related with calculation of the cooling off period will be started from finished punishment principal or from completion of the trial period the. Condition the show complexity nomination for ex-the convict who applied liberation conditionally, all at once become notes related with system election general head regions in Indonesia.